Role of Cytological Grading in Prognostication of Breast Carcinoma - Masamatti, Smita Surendra; C, Vijaya; DM, Narayana Swamy (Annals of Pathology and Laboratory Medicine, 2018)
Background: Breast carcinoma is now one of the most common cause of death in females worldwide, hence should be early diagnosis and treatment is necessary. This study aims at establishing Fine needle aspiration cytology (FNAC) as an individual parameter in diagnosing and grading breast carcinoma followed by correlation with histological grading. Methods: Cytological smears of 51 cases of breast carcinomas were graded by using Robinson’s method and corresponding histology sections were graded according to Elston and Ellis Nottingham modification of Bloom Richardson’s method and correlation was done. Result: On cytology, there were 10,26 and 15 cases of grade I, grade II and grade III tumours respectively while on histology there were 12, 31 and 8 cases of grade I, grade II and grade III tumours. The concordance rates between cytology and histology grades were 90%, 76.92% and 26.67% respectively with an absolute concordance rate of 64.71%. Conclusion: FNAC is simple, non invasive and a very good tool which provides information about the aggressiveness of the tumour and helps to select appropriate treatment.